EVALUASI KINERJA OPERASIONAL ANGKUTAN KERETA API KAMANDAKA JURUSAN SEMARANG – PURWOKERTO - Ario Ivano Nenepath; Juli Indra Setia Bate’e; Bambang Pudjianto; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2016)
PT. Kereta Api Indonesia (Persero) DAOP 5 Purwokerto has been operating Kamandaka train in Purwokerto - Semarang railway track since February 2015. Highway users prefer to use the train for reasons of time efficiency, as evidenced by the addition of the number of trips KA Kamandaka that initially only one trip into three trips a day to meet the high demand. To determine the performance of the train in accordance with the Certificate of Director General of Land No. 687 of 2002, needs to be reviewed in terms of load factor, the number of passengers carried, the waiting time of passengers, punctuality of arrival and departure of trains and passenger comfort as well as the calculation of income from the operation of the Kamandaka train and identification of the characteristics of rail infrastructure. From the analysis the greatest travel time to the direction of Semarang for 5 hours 20 minutes and to the direction of Purwokerto for 4 hours 39 minutes. The trains stop time by 25 minutes of Semarang direction at Weleri Station, the smallest downtime for 2 minutes of Purwokerto direction at Bumiayu Station. The value of the time delay arriving and departing to the direction of Purwokerto 25 minutes. As for the direction of Semarang time delay arriving and departing by 33 minutes. The difference of stop time in both directions due to train crossing with business and executive trains between Weleri station and Tegal station. Figures 0.485 m2 the comfort of the sitting room / space. Train capacity for 636 passengers. The highest value of the load factor is 88% in Purwokerto direction and the direction of Semarang by 79%. The highest load factor per segment of Purwokerto direction contained in Semarang Poncol - Weleri by 52%, while the lowest was 23% in Tegal - Slawi towards Purwokerto. With three trips operating costs amounted Rp.110.214.840 and income per day Rp. 162 070 000, - PT. KAI makes a profit of Rp. 51.855.160,- per day. Zone SMT-PWT or PWT-SMT is a zone that contribute most to incomes of around 70% - 80% with Rp 90,000, - per passenger rate, while the zones which contribute least 2% - 12% with rate of Rp 45,000, - per passenger is SMT-PKL or PWT-TG. At the operating of Kamandaka 235 the income comparison operational cost is 0.96 where the load factor average of 0.23. The Break Even Point achieved when the train load factor about 0,24. The efficiency of travel time is the reason people choose train than road transport modes.